Dampak Negatif Game Online terhadap Pelaksanaan Ibadah Shalat Remaja di Nagari Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok - Rahmida Fitri; Indah Muliati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Online games is a game that is played with the supported of an internet network. Along with the development of increasingly sophisticated technology, this online game will have a bad impact for an individual if he cant’t manage the time while playing the game. At this time, online Indonesian people, including teenagers. Online games at this time have become a necessity that cannot be abandoned by many people starting from children, teenagers and even adults but at this time the most enthusiasts of online game are among teenagers. This study aims to determine the impact of online games on the implementation of prayer worship, to determine the factors that cause the negative impact of online games and to determine the efforts to overcome the impact of online games on the implementation of youth prayers in Nagari Alahan Panjang. This study uses a qualitative method with the type of research that is descriptive. Sources of data were taken from fifteen informants through in-depth interviews who had been selected using the purposive sampling technique, the informants consisted of ten teenagers ranging in age from 12-18 years and five parents of teenagers playing online games. The result of this study indicate that negative impacts. In addition to the positive impact, it turns out that is online game also his negative impact namely: 1) Causing addition, 2) Procrastinating prayers times, neglecting and even leaving the implementation of prayer, 3) Laziness to pray, 4) Waste of time and material, 5) Words that are not polite, 6) Rebbuting parents, 7) Irritability, 8) Can interfere with health. The result of this study can be used as information for researchers in examining this problem in a more in-depth context.